Mortality and prognostic factors in Chinese patients with systemic lupus erythematosus. (September 2018) - Mu, L; Hao, Y; Fan, Y; Huang, H; Yang, X; Xie, A; Zhang, X; Ji, L; Geng, Y; Zhang, Z
Objectives: To investigate the mortality and causes of death in Chinese patients with systemic lupus erythematosus. Methods: We collected the clinical data of all consecutive adult systemic lupus erythematosus patients at the Rheumatology department of Peking University First Hospital between January 2007 and December 2015. The primary causes of death were identified, the standardized mortality ratio and years of life lost were calculated, and the survival and variables associated with mortality were determined by Kaplan–Meier and Cox regression analysis respectively. Results: The mean age of all 911 patients (814 females and 97 males) was 37.8 ± 14.7 years, the median disease duration at recruitment was 2.6 (0.5–7.0) years, and the median follow-up duration was 3.0 (1.4–5.1) years. Among the 911 patients who were successfully followed up, 45 patients died. Infection (31.1%) was the leading cause of death followed by renal failure, pulmonary arterial hypertension and cerebrovascular diseases. The overall age and sex-adjusted standardized mortality ratio was 3.2 (95% confidence interval 2.4–4.0), and the years of life lost for women and men were 29.8 and 9.4 respectively. Overall survival at 1, 5 and 10 years was 98.2%, 95.3% and 93.7% respectively. Older age at disease onset, infection, autoimmune hemolytic anemia, thrombocytopenia and pulmonary arterial hypertension were independent risk factors for the mortality of systemic lupus erythematosus patients, and longer disease duration at recruitment was an independent protective factor. Conclusions: Mortality of systemic lupus erythematosus patients in China was substantial, especially in females, with infection the leading cause of death. Older age at disease onset, infection, autoimmune hemolytic anemia, thrombocytopenia and pulmonary arterial hypertension were associated with poor outcomes.